e-Waste Bin: An interactive waste management and monitoring system via IoT platform - Mohd Kasim, Noor Shahida; Ab Rashid, Siti Rosmaniza; Jing, E.W. (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Nowadays, waste management has become a challenge faced by the developing and the developed countries. The main problem occurred when waste accumulates beyond capacity before schedule collection. This situation may led to huge environmental pollution and potential outbreaks of disease in the society. In this case, waste pickers are essential in waste management by ensuring timely waste collection and preventing bin overflow. However, monitoring bin levels in real-time poses a challenge for them. Hence, this research proposes a mobile application for solid waste management, designed to monitor the garbage fill level of the waste bin. The app alerts both users and waste pickers to potential overflowing bins, allowing users to communicate directly with waste management company. Employing an ESP8266 NodeMCU, HC-SR04 ultrasonic sensor, MQ-4 gas sensor, and solar power for energy efficiency, this system results in a user-friendly mobile application. This innovation is aimed at mitigating the issue of waste overloading and improves the environmental quality.